Parenting in West Indian Families: Relationship to their Literacy Beliefs and Practices - Jaeger, Elizabeth; MacTurk, Katherine; Nguyen, Jacqueline (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
This study explored whether authoritarian parenting may help explain the poor literacy outcomes among USVI children. Forty-one West Indian mothers of young children were interviewed and completed questionnaires assessing authoritarian childrearing attitudes; warm parent-child relationships; and literacy beliefs and practices. High adult control and warmth were not significantly related in this sample, and each dimension differentially predicted literacy variables. Mothers endorsing higher levels of adult control believed that children learn to read at a later age, and engaged in more direct reading instruction. Mothers who reported warmer relationships were more likely to read with their child for fun. Future research is needed that directly examines how general and domain-specific features of parenting relate to literacy outcomes in VI children.